2013
DOI: 10.1371/journal.pone.0059500
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Severe Radiographic Osteoarthritis Have a Better Prognosis in Physical Functioning after Hip and Knee Replacement: A Cohort-Study

Abstract: IntroductionAlthough Total Hip and Knee Replacements (THR/TKR) improve Health-Related Quality of Life (HRQoL) at the group level, up to 30% of patients are dissatisfied after surgery due to unfulfilled expectations. We aimed to assess whether the pre-operative radiographic severity of osteoarthritis (OA) is related to the improvement in HRQoL after THR or TKR, both at the population and individual level.MethodsIn this multi-center observational cohort study, HRQoL of OA patients requiring THR or TKR was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 42 publications
13
92
0
1
Order By: Relevance
“…Previously, studies have found that a substantial proportion of TKAs are performed in patients who on radiography appeared to have only mild or moderate knee OA [9,12,14]. Furthermore, only a portion of patients with severe radiographic knee OA end up seeking or undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies have found that a substantial proportion of TKAs are performed in patients who on radiography appeared to have only mild or moderate knee OA [9,12,14]. Furthermore, only a portion of patients with severe radiographic knee OA end up seeking or undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%
“…The KSS, age, process of healthcare and treatment outcomes scores which were significant Table 3. The median treatment outcomes points for Group I were 23 (range 13-28), 16 for Group II (range 13-22) and 14 (13)(14)(15)(16)(17)(18)(19)(20)(21) for Group III.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have focused on patient's expectations and satisfaction influenced by education and income, discord between patient and surgeon recovery expectations, information from the media, information about rehabilitation received from the surgeon, improvements in both pain and physical function scores, preoperative severity of the osteoarthritis, employment, postoperative satisfaction and hospital experience [9,[13][14][15][16][18][19][20][21][22][23]. Moreover, in a systematic review by Haanstra et al [11], the authors highlighted the need for more studies in the field of patient expectations for total joint arthroplasties (TJA).…”
Section: Discussionmentioning
confidence: 99%
“…A total knee replacement is an effective surgical intervention for the patients with knee osteoarthritis by reducing pain in the knee joints and enhancing the quality of life and joint functions for a smoother gait. A study of the cohort of patients with total knee replacement showed a significant increase in the Short Form-36 Health Survey (Gidwani, Tauro, Whitehouse & Newman, 2003;Keurentjes et al, 2013). However, all the prognoses of the patients with total knee are positive.…”
Section: Introductionmentioning
confidence: 99%